Incorporação de lodo de esgoto e seus efeitos sobre alguns atributos do solo cultivado com rabanete (raphanus sativus l.) - Lopes, Maria dos Anjos de Jesus Barros Monteiro (2008)
The release of pollutants in the environment has been under severe control in developed countries. In developing countries like Brazil and Cabo Verde this control has also been increasing. A viable alternative for the purpose of this waste is its application in agriculture as reconditionant soil, thus becoming important from the economic and environmental points of view. This study aimed to evaluate the effects caused by the use of sewage sludge on land cultivated with radish (Raphanus sativus L.). The work was conducted in an experimental area located in the United Families Community, in the district of Santa Monica, City of Camaragibe, Pernambuco, Brazil, using Dystrophic RED ARGISOIL soil. A randomized block experimental design with five treatments (zero, 25, 50 and 75 Mg ha-1 of sewage sludge and 25 Mg ha-1 of humus California red - Eisenia foetida) and three repetitions was used. The masonry plots measured 1 m wide, 6 m long and 0.20 m deep, with 21 rows spaced between rows of 0.35 m and 0.15 m between plants. The harvest of the radish was held 30 days after sowing. It was observed, after statistical analysis, a production of around 18 t / ha in the dose equivalent to 25 Mg ha-1 of sewage sludge. The other examined parameters had also a positive behaviour in the presence of sewage sludge